Teaching music to students with special needs : a label-free approach - Hammel, Alice; Hourigan, Ryan M. (Oxford University Press, 2017)
"The Second Edition of Teaching Music to Students with Special Needs offers updated accounts of music educators'experiences, featured as vignettes throughout the book. An accompanying Practical Resource includes lesson plans, worksheets, and games for classroom use. As a practical guide and reference manual, Teaching Music to Students with Special Needs, Second Edition addresses special needs in the broadest possible sense to equip teachers with proven, research-based curricular strategies that are grounded in both best practice and current special education law. Chapters address the full range of topics and issues music educators face, including parental involvement, student anxiety, field trips and performances, and assessment strategies. The book concludes with an updated list of resources, building upon the First Edition's recommendations."--Publisher's description.